Decoding the socio-economic approach to management : results of the second SEAM conference in the United States - Conbere, John P.; Savall, Henri; Heorhiadi, Alla (Emerald Publishing Limited : Information Age Publishing Inc., 2016)
In May 2014, the French research laboratory ISEOR (Socio-Economic Institute for Firms and Organizations) and the University of St. Thomas co-sponsored a second conference on the application of the Socio-Economic Approach to Management (SEAM) paradigm and methodology in the United States. SEAM is a scientific approach to consultancy that focuses on uncovering the dysfunctions and hidden costs that exist in organizations, 'hidden' in the sense that they are not captured by traditional accounting methods and financial analyses. Through intervention that encompasses the entire organization - what the ISEOR team refers to as the HORIVERT approach (combining horizontal and vertical intervention) - the underlying goal is to enhance organizational performance by attacking the 'TFW virus,' a vestige of the early work by Frederick Taylor, Henri Fayol, and Max Weber that has sufficiently infiltrated our thinking about management and organization to the point where are falling well short of our own potential. The resultant dysfunctions this virus unleashes creates hidden costs that readily destroy a firm's value-added possibilities. The volume captures the ideas, applications, and exchanges of that meeting, attempting to bring the reader into the conference itself. Chapters include the contributors' presentations ('Chapter Prologue: Conference Remarks'), revised conference papers, and the question and answer dialogue for the session.
Keywords: Management -- Social aspects -- Congresses.; elektronické knihy; Conference papers and proceedings.; Business & Economics -- Management.; Management and management techniques.; electronic books